Numerical simulation of fuel combustion processes to reduce harmful dust and gas emissions using Over Fire Air - Askarova, A.S.; Bolegenova, S.A.; Maxsimov, V.; Bergaliyeva, S.A.; Bolada, S. (Recent Contributions to Physics, 2019)
Currently, air pollution is a huge environmental problem. The participation of energy companies in environmental pollution by fuel combustion products and solid waste is significant. Above all, power plants operating on solid fuel are one of the main sources of air, water and soil pollution. Until recently, during coal combustion process the most part of attention has been paid to protecting the environment from solid pollutants, such as ash. Very little attention has been paid to the gas products of combustion reactions, especially to NOх и SO2. Mainly NO and NO2 of nitrogen oxides are found in the atmosphere. NO is an unstable component that oxidizes to NO2 during 0.5-3 to 100 hours. The toxicity of NO2 is 7 times higher than the toxicity of NO. Nitrogen oxides are most dangerous as an active ingredient in the formation of photochemical smog. Currently nitrogen oxides are recognized as the most toxic atmospheric pollutants, and their maximum permissible concentration is 6 times less than for sulfur dioxide. It is believed that emissions of nitrogen oxides generated during combustion contribute to the oxidation of precipitation, photochemical air pollution and depletion of the ozone layer. In this regard, many studies are aimed at the development of technologies for environmentally friendly combustion, which provide harmful dust and gas emissions at the level of international standards. One of the ways to reduce the concentration of nitrogen oxides NOx is the stepwise combustion of a powdered coal mixture, in particular the "Over Fire Air" technology. The idea of this method is based on the fact that the main volume of air is supplied to powdered coal burners, and the rest of the air is supplied further along the height of the torch through special nozzles. The article presents the study results of the Over Fire Air technology influence on the aerodynamic characteristics of the combustion chamber of the BKZ-160 boiler.